Pelaksanaan Evaluasi Penguatan Profil Pelajar Pancasila (P5) dalam Pelajaran Fiqih di MTSN 2 Kota Serang - Ani Qudsiatul Maula; Vivi Amelia; Fahrul Mudoyip; Saefudin Zuhri; Wahyu Hidayat (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the implementation of the evaluation of the Strengthening of Pancasila Student Profile (P5) in Fiqh learning at MTsN 2 Kota Serang. P5 is a program designed to shape students' character based on Pancasila values, such as mutual cooperation, independence, critical thinking, creativity, and noble character. This research employs a qualitative approach with a case study method, using observation, interviews, and document analysis as data collection techniques.The results show that the P5 evaluation in Fiqh learning is carried out through various methods, such as behavior observation, project-based assignments, and group discussions. This evaluation process is integrated with Fiqh learning to help students internalize Pancasila values. However, the implementation of the evaluation still faces several challenges, including teachers' limited understanding of the P5 concept, time constraints in the learning process, and the lack of systematic evaluation instruments.To address these challenges, it is recommended to provide intensive training for teachers, develop comprehensive evaluation guidelines, and strengthen collaboration among all school stakeholders. Thus, the P5 evaluation can become more effective in supporting the formation of students' character in alignment with the national education vision.